Validation of a Novel Radiographic View for Evaluating Proximal Humerus Fractures: The Clear View: Original Research - Chun, Liane; Misaghi, Amirhossein; Cidambi, Krishna R.; McNeil, Natalie P.; Farnsworth, Christine L.; Edmonds, Eric W. (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Background: Orthogonal radiographs of the proximal humerus are challenging to obtain because the patient’s body mass can impede a quality lateral view and positioning of the shoulder can cause fracture displacement and patient discomfort. We describe a novel radiograph, the clear view (CL), taken 90° to the scapular Y (SY), developed with the goal to minimize pain and reduce radiation exposure. Evaluate the ability to accurately evaluate proximal humerus fracture displacement utilizing the CL in comparison to the standard available x-rays and assess pain score when obtaining the CL. Methods: Eleven independent observers at different levels of experience evaluated angulation and translation of three proximal humerus fractures: two cadaveric fractures and a third fracture in a 15-year-old to determine intra-observer correlation (ICC). Each fracture underwent the traditional radiographic series of anteroposterior (AP) in internal rotation (IR), AP in external rotation (ER), true axillary lateral (AX), SY, and transthoracic lateral (TRANS) plus computed tomography (CT). CL was obtained on the two cadaver fractures. Pain scores based on the Wong-Baker FACES Pain Scale were assessed for individual radiographic projections in thirteen patients with proximal humerus fractures. Results: ICC was >0.6 for all measures. True fracture angulation was underestimated a majority (>75%) of the time in all radiographic views, TRANS (p<0.001) and AX (p<0.049) views had the least amount of error. Moreover, measures of translation were both underestimated and overestimated in all views, but the most accurate measures of translation were obtained with IR, ER, and CL views. Pain scores ranged from 0-1.2 when the CL was obtained. Conclusions: Our study demonstrates that proximal humerus fracture angulation is often underestimated and translation is difficult to measure regardless of view utilized. However, the clear view, when combined with the AP view offers an orthogonal, reproducible, valid measure of displacement and causes minimal patient discomfort.